2015
DOI: 10.1210/er.2014-1063
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Homeostasis During Short-term and Prolonged Exposure to High Altitudes

Abstract: Most of the literature related to high altitude medicine is devoted to the short-term effects of high-altitude exposure on human physiology. However, long-term effects of living at high altitudes may be more important in relation to human disease because more than 400 million people worldwide reside above 1500 m. Interestingly, individuals living at higher altitudes have a lower fasting glycemia and better glucose tolerance compared with those who live near sea level. There is also emerging evidence of the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 245 publications
10
98
1
Order By: Relevance
“…5C), who also showed faster clearance of glucose during an OGTT (P < 0.001; Fig. 5D) in agreement with previous reports (41). In Sherpas, however, there was no indication of altered glucose homeostasis.…”
Section: Resultssupporting
confidence: 91%
“…5C), who also showed faster clearance of glucose during an OGTT (P < 0.001; Fig. 5D) in agreement with previous reports (41). In Sherpas, however, there was no indication of altered glucose homeostasis.…”
Section: Resultssupporting
confidence: 91%
“…Many studies have reported lower fasting glycaemia in clinically healthy residents living between 3000 and 4500 m, compared with residents living below 500 m. This difference has been reported in adults (26,39,43) and also in neonates (44). Lower fasting glycaemia in adults at high altitudes was shown in a large clinical study from a nationally representative sample in Peru (45).…”
Section: Glucosementioning
confidence: 91%
“…Based on the definition of high altitude (≥1,500 m) and the frequency distribution of the number of individuals who reside within a given altitude band, altitude was grouped in four categories: 0‐499, 500‐1,499, 1,500‐2,999, and ≥3,000 m. For the latter category, the median of the altitude was 3,397 m (interquartile range: 3,245.0‐3,725.0 m). The district with the highest altitude surveyed by ENAHO was located at 4,660 m. Since moderate or vigorous physical activity for at least 150 min per week has been shown to result in a more sustained weight loss , we grouped the variable physical activity (total minutes per week of moderate and vigorous activity at work, home, and during recreation) in four categories: 0‐149, 150‐299, 300‐449, and ≥450 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although acute suppression of appetite and weight loss in lowlanders exposed to high altitudes is well documented (37,38), the direct effect of prolonged altitude exposure on appetite remains unknown. Basal metabolic rate and sympathetic activation does not appear to be higher among highlanders as compared with lowlanders, even if normalized to fatfree mass (17). Since there is an inverse relationship between elevation and ambient temperature (39), cold-induced increased thermogenesis could explain the lower prevalence of obesity, including abdominal obesity, at higher altitudes.…”
Section: Obesitymentioning
confidence: 99%